(untitled) (Construction Economics and Building, 2012)
Increased complexity of the construction business and consequentuse of new management concepts and technologies ledconstruction organisations to focus more on the transfer of explicitknowledge. However, it is the tacit knowledge that determinesthe construction companies’ competitiveness in a business thatis driven by turbulent market conditions and customers’ everincreasingdemands. This paper highlights the importance of tacitknowledge sharing in construction, explores the challenges andopportunities to efficiently share tacit knowledge, and based on theliterature review identifies some critical factors that influence tacitknowledge in construction. It is argued that employees’ knowledgesharing (learning) behaviours are influenced by work practices thatare borne by respective organisational behaviours. Organisational,cultural, and project characteristics that facilitate knowledgesharing among construction employees are explored and thepractices that influence the construction employee behaviour insharing tacit knowledge are highlighted.